CHARACTER, STRUCTURE OF MIGRATION PROCESSES AND FEMINIZATION OF LABOR MIGRATION - E. Kovanova; E. Tenetova; N. Eldyaeva (Вестник университета)
The gender characteristics of migration processes in the depressed Russian region − the Republic of Kalmykia − have been examined. Based on the analysis of statistical data for a long period and a specially organized sample survey, it has been revealed that the female population became more actively involved in migration processes and, above all, in long-term labor migration. The participation of women in the least studied and little covered by official statistics (in labor migration) has been determined. The conclusion has been made, that there is a close relationship between female migration and demographic development. The analysis revealed that the distribution of the number of employed migrants of both sexes by economic activity is heterogeneous, which indicates the existence of a specific gender specificity.